Energy and exergy analyses of hydrogen production process with aluminum and water chemical reaction. (15th August 2020) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: Hydrogen is recognized as an energy carrier and has substantial potential to fulfill future energy demands. This paper conducted energy and exergy analyses on a hydrogen production process that utilized the chemical reaction between aluminum and water. Various aspects of the system's performance, such as energetic efficiency, exergetic efficiency, sustainability index, and other methods to evaluate the system's performance were examined. The factors such as the lower heating value (LHV) of hydrogen, the reactant molecules' enthalpy of formation, and their respective chemical exergy were considered. The energy input from the heater was substantial enough to be taken into consideration; however, the energy input from the pump was considered negligible in the overall process efficiency. The standard reaction efficiency equation displayed the most favourable results at the higher water temperatures. Therefore, the variation in the water medium and NaOH concentration experiments used 70 °C as its water temperature. The variation in water medium test identified tap water as an effective water medium due to its higher energy efficiency, and its ability to achieve the maximum theoretical yield. However, seawater was identified as a viable option for future testing, as it was able to achieve standard energetic and exergetic efficiencies up to 32.40% and 54.35% for the 3-g samples. Additional parametric studies were conducted and compared throughout this study to provide a comprehensive analysis of the system's performance. Highlights: The significant findings from this research study are as follows: 70 °C and 40 °C, has standard energy efficiency of 20.17% and 12.24% respectively. Seawater achieved a standard energy and exergy efficiency of 32.40% and 54.35%. Reaction is most efficient at a stoichiometric mole ratio.